ELECTRONIC COMPUTER SEARCHES IN PRIMARY CARE CAN LEAD TO GREATER IDENTIFICATION OF NON-MALIGNANT PATIENTS FOR PALLIATIVE CARE. Issue 1 (1st March 2014) - Mason, BL; Boyd, K; Murray, SA; Steyn, J; Cormie, P; Kendall, M; Munday, D; Weller, D; Fife, S; Murchie, P; Campbell, C
Abstract : Introduction: Most patients receive palliative care only in the last two months of life. The use of information technology currently in place in general practices provides an opportunity to identify people for supportive and palliative care at an earlier stage. Aim(s) and method(s): To assess the impact and acceptability of a primary care electronic record search to identify patients with unmet palliative care needs. Methods: A computer record search was developed and tested in fifteen general practices in two Scottish health boards. A sub-set of patients identified by the search were selected for further review and care planning by GPs. Quantitative and qualitative data were collected to assess the impact of the search results on practice behaviour and attitudes towards the search among professionals and patients. Results: The electronic record search successfully identified candidate patients for palliative care, some of whom the practice reviewed and identified for palliative care. Starting an Anticipatory Care Plan or electronic record sharing with Out of Hours services were the most common actions GPs took with patients who were reviewed after identification by the search. Conclusion(s): Electronic searching of primary care records can identify a shortlist of patients to assess for palliative care needs. Regularly producing such lists at team meetings should increase the number of non-malignant patients on palliative care registers. However GP and patient attitudes towards the taboo words "palliative care" mean that this will only lead to action if "supportive" care options that do not require the label "palliative care" are made available.